Can mechanical load and physiological intensity during gymnastics training explain physical adaptations? an observational study - Zhou, Y.; Yang, L. (Frontiers in Physiology, 2025)
This study analyzed the relationships between physiological and mechanical training loads and subsequent physical strength and aerobic adaptations in youth gymnasts. A prospective cohort design monitored 40 local-level female artistic gymnasts (16.5 ± 1.1 years) over a 12-week preparatory training phase. Strength (Isometric Mid-Thigh Pull [IMTP], Countermovement Jump [CMJ]) and aerobic fitness (Multistage Aerobic Fitness Test by Luc Léger [MSAFT]) were assessed at baseline and post-intervention. Training load was continuously monitored via heart rate (TRIMP), mechanical load (jumps), and ratings of perceived exertion (RPE). Significant improvements were observed across all fitness parameters: IMTP (19.2%), CMJ (2.7%), and MSAFT (8.6%), all with large effect sizes (p < 0.001). Mean session loads averaged RPE 7.25 ± 0.732, TRIMP 290.45 ± 30.343, and 105.18 ± 27.547 jumps. Jump volume significantly correlated with improvements in IMTP (r = 0.478, p = 0.002) and CMJ (r = 0.785, p < 0.001), indicating its large association with strength improvement. Conversely, RPE (r = 0.775, p < 0.001) and TRIMP (r = 0.872, p < 0.001) were largely correlated with enhanced aerobic fitness. This study showed that physiological training loads are important for aerobic adaptations, while mechanical loads, particularly jumps, drive strength and power improvements in youth gymnasts. Therefore, monitoring strategies that integrate both internal and external load parameters is essential for optimizing specific physical qualities in gymnasts.